A correlational study of MUET and IELTS - Bidin, Siti Jamilah; Mat Don, Zuraidah; Abdul Raof, Abdul Halim; Zubairi, Ainol Madziah; Mahat, Nor Idayu (Majlis Peperiksaan Malaysia, 2019)
The present century has seen the rapid globalisation of Higher Education, and increasing numbers of Malaysian students are seeking to study in universities abroad, and increasing numbers of students from abroad are seeking to enter universities in Malaysia. The MUET has long been established as the English test for university entrance in Malaysia, and in the context of globalisation, it is essential to know how it compares with other established English tests. The overall aim of this study is to compare MUET Band scores with IELTS Band scores. A correlational study was undertaken to measure the statistical association between MUET and IELTS Band scores.